Enhancing Cystic Fibrosis Immune Regulation - van Heeckeren, Anna M.; Sutton, Morgan T.; Fletcher, David R.; Hodges, Craig A.; Caplan, Arnold I.; Bonfield, Tracey L. (Frontiers in Pharmacology, 2021)
In cystic fibrosis (CF), sustained infection and exuberant inflammation results in debilitating and often fatal lung disease. Advancement in CF therapeutics has provided successful treatment regimens for a variety of clinical consequences in CF; however effective means to treat the pulmonary infection and inflammation continues to be problematic. Even with the successful development of small molecule cystic fibrosis transmembrane conductance regulator (CFTR) correctors and potentiators, there is only a modest effect on established infection and inflammation in CF patients. In the pursuit of therapeutics to treat inflammation, the conundrum to address is how to overcome the inflammatory response without jeopardizing the required immunity to manage pathogens and prevent infection. The key therapeutic would have the capacity to dull the inflammatory response, while sustaining the ability to manage infections. Advances in cell-based therapy have opened up the avenue for dynamic and versatile immune interventions that may support this requirement. Cell based therapy has the capacity to augment the patient’s own ability to manage their inflammatory status while at the same time sustaining anti-pathogen immunity. The studies highlighted in this manuscript outline the potential use of cell-based therapy for CF. The data demonstrate that 1) total bone marrow aspirates containing Cftr sufficient hematopoietic and mesenchymal stem cells (hMSCs) provide Cftr deficient mice >50% improvement in survival and improved management of infection and inflammation; 2) myeloid cells can provide sufficient Cftr to provide pre-clinical anti-inflammatory and antimicrobial benefit; 3) hMSCs provide significant improvement in survival and management of infection and inflammation in CF; 4) the combined interaction between macrophages and hMSCs can potentially enhance anti-inflammatory and antimicrobial support through manipulating PPARγ. These data support the development of optimized cell-based therapeutics to enhance CF patient’s own immune repertoire and capacity to maintain the balance between inflammation and pathogen management.